UiTMLaw charts student career paths with industry players 4.0 - UiTM, Faculty of Law (Faculty of Law, 2023)
The Faculty of Law at UiTM (UiTMLaw) organized this event on 7 January 2023 where key players of the Malaysian legal industry meets the graduating Law students of UiTM and networks for the future employment and pupillage opportunities. The program was officiated by Professor Datuk Dr. Hajah Roziah Mohd Janor, the Vice-Chancellor of UiTM. The program sought to expose students to hands-on experiences pitching the MSE to prospective employers in the job market and a chance to network with legal professionals. The Dean and UiTMLaw express their gratitude to the vice-chancellor or for her graciousness in officiating the event and the participating industry panels for meeting the students. Deep appreciation also goes to the Office of the Chief Justice of Malaysia, the Attorney General's Chambers of Malaysia, Maybank, Petronas, and Messrs Zaid Ibrahim & Co, Messrs. Richard Wee Chambers Messrs. Rosli Dahlan Saravana Partnership, Messrs. Skrine, Messrs. Shearn Delamare & Co., Messrs. Thomas Philip, and Messrs. Lee Hishamuddin. Allen & Gledhill, Messrs. Zul Rafique & Partners, Messrs. Azmi & Associates, Messrs. Shook Lin & Bok, Messrs. Raja, Darryl & Loh, Messrs. Gan Partnership, Messrs. K. K Lim, and Messrs. Lim Chee Wee Partnership, Messrs. Izwan & Partners, Messrs. Zharif Nizamuddin, Messrs Nurainie Haziqah & Co., Messrs Shahrul Hamidi & Haziq, Messrs. Fareez Shah & Partners and Messrs. Amir Faliq & Syahindah.